PENGEMBANGAN STRATEGI PEMBELAJARAN KOGNITIF BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Nur Amalina Abdul Rahman; Andi Fitriani Djollong; Dewi T; Muhammad Kharis; Siti Rondhiyah; Mardiah Wahyuni (STKIP Pesisir Selatan, 2026)
The development of 21st-century education requires learning approaches that emphasize the cultivation of Higher Order Thinking Skills (HOTS) as essential competencies for students. However, the implementation of Islamic Religious Education (PAI) learning remains predominantly focused on Lower Order Thinking Skills, resulting in limited development of students’ analytical, evaluative, and creative abilities. This study aims to analyze and develop cognitive learning strategies based on HOTS within the context of Islamic Religious Education. This research employs a qualitative approach through conceptual library research. Data were collected from reputable national and international academic journals, key reference books, and relevant educational policy documents published within the last ten years. Data analysis was conducted using content analysis and thematic-conceptual analysis of recent literature. The findings indicate that HOTS-based cognitive learning strategies in Islamic Religious Education are characterized by problem-oriented, reflective, contextual, and integrative learning processes that combine Islamic conceptual understanding with the development of critical and creative thinking skills. The implementation of HOTS in PAI faces several challenges, including limited pedagogical competence among teachers, learning designs that are not yet HOTS-oriented, and assessment practices that still emphasize lower-level cognitive skills. Nevertheless, the application of HOTS-based strategies demonstrates strong potential to enhance the quality and relevance of Islamic Religious Education. The novelty of this study lies in the integrative contribution between HOTS theory and the value-based characteristics of Islamic education, offering a conceptual framework for transforming PAI learning in response to the demands of 21st-century education.